"NATURE OF FEELINGS" - ECOLOGICAL AND EDUCATIONAL PROJECT OF THE KHARITONOV DENDIOLOGICAL GARDEN - Kulikova Olga (Hortus Botanicus, 2018)
The dendrological garden is of great importance in the general biological and ecological education of the population. In addition to studying and protecting plants, the garden has ample opportunities to realize its achievements in educational and educational activities. One of the forms of education of ecological thinking and worldview is the creation of ecological paths. On the territory of the dendrological garden. S.F. Kharitonov in 2015 equipped with an ecological interactive path "Nature of the senses." For the methodical and didactic support of modular classes with visitors of the green class of the ecological path "Nature of the senses", the specialists of the EcoCentre "Zapovedniks" and the dendrological garden in 2017 developed the ecological and educational program "Discoveries of the Nature of Senses".